RETRIBUSI IZIN TRAYEK DI KABUPATEN BOGOR 2022 BERDASARKAN PERDA NO. 13 TAHUN 2011: Route Permit Retribution In Bogor Regency 2022 Based On Regional Regulation No. 13 Of 2011 - Oktavianus Alexander; Reni Dwi Purnomowati (Reformasi Hukum Trisakti, 2025)
One of the sources of Bogor Regency's Original Regional Income (PAD) is route permit fees related to public transportation. However, the local government's policy in collecting it has caused dissatisfaction due to the mechanism being considered less transparent and difficult to access. Therefore, it is important to ensure transparency and accessibility to maintain regional financial stability. This research examines the procedures for granting route permits based on Bogor Regency Regional Regulation No. 13 of 2011 as well as obstacles in collecting levies. Using normative legal research methods with qualitative analysis, this research processes primary and secondary data and draws conclusions through deductive logic. The research results show that the collection of route permit fees has not been effective due to various internal and external obstacles, so that implementation is not optimal in accordance with the objectives of the applicable regulations.